Analyzing wrestlers' perceptions of wrestling by studying the metaphors of the athletes from the Turkish national team - Yilmaz, I.; Türkmen, M.; Bektas, F.; Gül, M.; Arslan, F.; Karaman, G. (International Journal of Wrestling Science, 2014)
This study aimed to explore the perceptions of wrestlers on the Turkish national wrestling team by analyzing their metaphors for wrestling. 107 athletes voluntarily participated in this study in 2013. Data were collected by asking the volunteers to fill in the blanks of the following sentence: "Wrestling is like … since …" In this way, it was expected that each participant would come up with a metaphor. For this study, the phenomenology research design was used and the data were analyzed using the content analysis technique. Within this scope, the analysis and interpretation of data is carried out in five stages: (1) Specifying the metaphors (2) Classifying the metaphors (3) Developing the categories (4) Ensuring validity and reliability (5) Entering data into SPSS program for the quantitative data analysis. According to the findings of the research, the participants generated 59 valid metaphors for wrestling. 10 different categories were developed by examining common characteristics of the metaphors. It was found that participants perceived wrestling as follows: As an expression of life (31 %), as a guide-ideal (19.2 %), as happiness (13.9 %), as dependence (11.7 %), as culture (10.7%), as income (9.6 %), as continuity (8.5 %), as diversity-richness (5.3 %), as strategy (5.3 %), as porterage-carrier of burdens (2.1 %).